Towards a Structured Legal Framework for Protecting Home Worker’s Rights in Indonesia - Ratih Damayanti; Rodiyah Rodiyah; Muhammad Azil Maskur; Putri Balqis Nuril Hakim; Quinny Azalia Putri; Ahmad Gelora Mahardika (Universitas Negeri Semarang, 2026)
Home-based workers constitute a segment of the labor force who carry out their work from their residences, typically under informal employment arrangements, which often results in their exclusion from adequate legal protections. The definitional distinctions between home- based workers and other categories of workers, coupled with their significant numbers, underscore the urgency of recognizing and ensuring legal protections for this group. This study aims to examine the risks and challenges faced by home-based workers within industrial contexts and to enhance understanding of the labor rights that are often denied to them. This study uses a normative juridical method, with statutory and conceptual approach, based on a literature review of primary, secondary, and tertiary legal materials. The findings reveal that home-based workers encounter a range of issues, including the absence of written employment contracts, substandard wages, excessive working hours, lack of social security coverage, and constraints on forming labor unions. Additionally, exploitative practices such as the involvement of child labor and the imposition of production costs on workers are prevalent. Addressing these challenges requires strengthening legal awareness and ensuring that home-based workers are afforded the rights and protections to which they are entitled.